Discourses of collective identity in Central and Southeast Europe, 1770-1945 (Budapest ; New York Budapest ; New York Budapest ; New York Budapest ; New York)
4 cilt 5 ciltte : (1. c. x, 351 sayfa ; 2. c. ix, 498 sayfa ; 3,1. c. [4], 486 sayfa ; 3,2. c. ix, 392 sayfa ; 4. c. ix, 442 sayfa)